POLA KONSUMSI BERAS RUMAH TANGGA BERDASARKAN GOLONGAN PENDAPATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI KOTA PALANGKA RAYA - Revi Sunaryati (AgriPeat, 2021)
Rice is a basic requirement for the people of Central Kalimantan Province. The biggest consumption of rice comes from household consumption. Households with different income levels will have different consumption patterns. With this situation, this research is important to determine how the pattern of household rice consumption is based on income groups and what factors influence the pattern of household rice consumption based on income groups in the City of Palangka Raya. This study uses primary data and secondary data. The research analysis uses descriptive analysis and quantitative analysis. Quantitative analysis uses multiple linear regression analysis with Ordinary Least Square (OLS). The econometric model used is the double log model assisted by using the Eviews 9.0 application. The results of the study showed that the factors that significantly influenced the consumption pattern of household income were the number of house members and the age of the household head. In the high income group the factors that significantly influence are the dummy marital status of the head of the household, the age of the head of the household has a positive effect and the number of household members has a negative influence and each has a significant effect on household rice consumption.